Analisis Peran Hallo Effect Terhadap Preferensi Masyarakat Memilih Belanja Online - Shifa Nirmala; Laras Pratiwi; Anisa Ratutria; Fitri Agistiani (Politeknik Negeri Padang, 2024)
One possible reason why customers become more loyal to services is their convenience and satisfaction, so service providers can maximize their satisfaction. Satisfied and loyal customers will strengthen their relationship with the service provider. The impact of customer halo, experience, security perception, satisfaction, and convenience will be examined in this study. A quantitative study was conducted on e-commerce users in the city of Tasikmalaya, with 34 respondents.